SINTESIS HIDROKSIKALKON MENGGUNAKAN KATALIS NaOH DAN NaOH+ZrO2 SERTA UJI AKTIVITAS ANTIOKSIDAN - , Gian Primahana; , Dr. Winarto Haryadi., M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2012)
QSAR analysis has been done to 23 hydroxychalcone derivative compounds by using multilinear regression with net atomic charge as electronic descriptor. Coefficient correlation (R), square of regression coefficient correlation (R2 Synthesis of 2 and 3-hydroxychalcone was compound conducted by dissolving 2 or 3-hydroxybenzaldehyde and acetophenone in ethanol solution and adding with 40% NaOH solution. A certain amount (0.1 g) of ZrO), standard deviation (SD), significance F, value of Fcal/Ftab, and Predicted Residual Sum of Square (PRESS) were used for statictical parameters to validate models derived from the analysis. Calculation of QSAR descriptor was performed at RHF (Restricted Hartree-Fock) level of theory using STO-3G basis set with convergence limit of 0.01 kcal/mol. Hydroxychalcone in s-cis conformation was choosen for initial geometry. Compound 2 and 3-hydroxychalcone are recommended to be synthesized based on the QSAR model. 2 was added onto reaction system in order to investigate the role of ZrO2 on product increasement. Method of the inhibition degradation of 2-deoxyribose was used to calculate antioxidant activity of hydroxychalcone compound. IC50 value were calculated using linear regression method. Addition of ZrO2 onto reaction system has increase reaction products by 163,18% and 24,19% for 2 hydroxychalcone and 3- hydroxychalcone respectively. Antioxidant activies were tested for those compound yielding IC50 238,68 (2-hydroxychalcone) and 339,07 Î¼g/mL (3-hydroxychalcone). Antioxidant activity of 2-hydroxychalcone is higher than 3-hydroxychalcone due to a higher stabilization of 2-hydroxychalcone radical compared with 3-hydroxychalcone.